1979
DOI: 10.1007/bf02667435
|View full text |Cite
|
Sign up to set email alerts
|

A review of soybean oil reversion flavor

Abstract: Crude soybean oil has a characteristic “greenbeany” flavor, which during refining, bleaching and deodorization is eliminated to produce a bland tasting, light colored oil. However, flavor returns during storage and has been characteristically called the “reversion flavor” of soybean oil. This deleterious characteristics flavor has influenced the utilization of soybean oil and its fatty acids. Several theories for the cause of reversion flavor include: (a) oxidation of linolenic acid; (b) oxidation of isolinole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…The fatty acid composition of soybean (Glycine max (L.) Merr.) oil is the most important factor affecting oil oxidative stability (1,2). Efforts to improve the quality of soybean and other oilseed lipids through genetic manipulation have progressed, but large numbers of samples need to be analyzed (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The fatty acid composition of soybean (Glycine max (L.) Merr.) oil is the most important factor affecting oil oxidative stability (1,2). Efforts to improve the quality of soybean and other oilseed lipids through genetic manipulation have progressed, but large numbers of samples need to be analyzed (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…From a nutritional point of view, oat seed oil is also a good source of essential fatty acids, especially linoleic acid, as compared with the other edible oilseeds (Nergiz and Ö tleş 1994). In general, high linolenic acid is unsuitable for oil-food products due to its instability and the reversion of flavour associated with autoxidation (Smouse 1979;Green 1986;Singh et al 1990). Formo et al (1979) found that the contents of the main fatty acids corn oil were 8.00 Á12.00% palmitic acid, 2.00 Á5.00% stearic acid, 19.00 Á49.00% oleic acid and 34.00 Á62.00% linoleic acid.…”
Section: Characteristics Of Grains and Oils Of Oats 349mentioning
confidence: 96%
“…Lipoxygenases exist in raw soybeans could speed up oxidation of polyunsaturated fatty acids (Hildebrand et al, 1990), such as linoleic acid and linolenic acid, which contained 1,4-(E,E)-pentadiene structure, and produce hydroperoxides with conjugated double bond. On the other hand, such a similar non-enzymatic mechanism may occur in raw soybean by autoxidation of linolenic, isolinolenic acid (Smouse, 1979). These hydroperoxides decomposed into huge amounts of volatile components, such as various kinds of short-chain alcohols, ketones, aldehydes etc., which brought unpleasant beany flavor to soybean and soybean products.…”
Section: Figure 1 Gas Chromatogram Of Volatile Components In Sfe-bsomentioning
confidence: 99%